[Rezension von: Gauvard, Claude, 1942-, Condamner à mort au Moyen Âge] - Giraudet, Luke (Crime, histoire & sociétés, 2021)
In the kingdom of France, the later Middle Ages witnessed a dramatic shift in the application and justification of the death penalty, a shift that represented an integral part of the broader history of the evolution of the French state and affirmation of royal authority. The power to administer this penalty emerged in this period as a key site of struggle between the French monarch and those entities that bracketed his authority, most notably the church, nobility and urban elite. As the royal...